Proactive Personality Analysis in Health Workers at Labuang Baji Hospital Makassar: Analisis Kepribadian Proaktif pada Tenaga Kesehatan di Rumah Sakit Labuang Baji Makassar - Rahmayanti, Hadijah; Utami, Ratri Dwi; Nuriana, Sri; Erpiani, Irma; Rahayu, Sri Hastari (Journal of Aafiyah Health Research (JAHR), 2025)
Abstract Background: In the face of challenging situations of change, the proactive personality of staff/employees who work in health institutions such as hospitals is very important because they are at the forefront of providing services and treatment for patients. But in reality, in the hospital environment, especially at Labuang Baji Hospital, Makassar City, there are still some health workers who make mistakes in communication, patient identification, administration, and errors in writing prescriptions or medical instructions, which are often caused by human error or lack of focus. Objective: This study aims to analyzing proactive personality in health personnel at Labuang Baji Hospital, Makassar. Method: This study used an analytical observational design with a cross sectional study approach. This research was conducted at Labuang Baji Hospital, Makassar City, South Sulawesi Province, which began in December 2023 and was completed with a population of 640 people and a sample of 240 people. Results: The results of the study found, based on univariate analysis on the characteristics of respondents, generally health workers at Labuang Baji Hospital Makassar City are female; have a vulnerable age of 30-39 years; The last education is mostly Diploma 3 (D3) graduates; The length of work mostly has a working period of 11-15 years. Based on bivariate analysis, it was found that proactive personality had a value of ρ=0.029, where it showeda value of ρ < 0.05, this means that the hypothesis is accepted where proactive personality is related to job satisfaction in health workers at Labuang Baji Hospital, Makassar City. Conclusion: Proactive personalities are relatively not limited by situational forces and can influence environmental changes, so it is expected that workers with proactive personalities tend to be more engaged when implementing proactive behaviors such as seeking feedback, going beyond task descriptions, and taking the initiative to engage in work-relevant learning.